A study of rice blast disease at different field in Sungai Rambai, Malacca / Ashmat Alimat - Alimat, Ashmat (Faculty of Plantation and Agrotechnology, 2016)
Rice (Oryza sativa) is the staple food and a source of income for farmers in Malaysia. Generally, rice blast reduces rice production and cause economic loss to the farmer and grower at Sungai Rambai, Melaka. In fact, rice blast disease cause by fungus Magnaporthe oryzae can affect all the above ground part of paddy plant, especially at leaf, node, grains and panicle and sometimes at leaf sheath. In this study, data on disease incidence and disease severity were collected and analyzed. Meanwhile, soil pH, meteorology data (rain, relative humidity, wind, temperature), farmers practices information were also obtained. Result showed the percentage (%) of disease incidence and severity are different among the selected field. However, in general all field recorded low percentage (%) disease incidence and severity which are below than 30 % for both. The occurrence factor of rice blast disease on disease incidence and severity was possibly due to water management, rate and timing of fertilizer application and also the environmental factor.